THE PATH TO INDUSTRY 5.0: A GREEN ECONOMY EVOLUTION AND ENERGY INNOVATIONS FOR SUSTAINABLE DEVELOPMENT - Я.І. Глущенко; О.О. Корогодова; Н.О. Черненко; Т.Є. Моісеєнко (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut")
The article deals with the problem of the formation and development of the green economy in the context of sustainable development: insights from Industry 3.0, 4.0, and 5.0 technologies. This study focuses on the topic of the green economy, its evolution, legislative changes in European countries and the agenda of international organizations in relation to the European Green Deal. The authors emphasize the opportunities and challenges from a technological point of view for the countries of the European Union in transitioning to a green economy according to the European Green Deal. Comparison of the results with the trends identified in the literature review are given. The factors of innovative development in the modern green economy and sustainable development are described. The first priority tasks and new opportunities for innovation in the national economy under the influence of Industry 4.0 and the provisions of the European Green Deal are characterized. A study of papers devoted to the researched problem allowed for classification of historical periods of development, determination, and evaluation of the path of green growth. A comparative analysis of green growth indicators developed by the Organization for Economic Cooperation and Development was conducted. It was established that leaders in terms of criteria for the most efficient and sustainable use of resources in 2019 are Sweden and Denmark; level of protection of natural capital - Slovakia and Croatia; impact on environmental state and ecological assets - Czech Republic and Germany; effectiveness of green growth state policy - Sweden, Netherlands, and Denmark. The article noted that Ukraine had rather low results in terms of the most efficient and sustainable use of resources, and the impact of the state of the environment and ecological assets. At the same time, our country demonstrated high results in terms of the level of protection of natural capital and the effectiveness of the state green growth policy. The authors defined a system of effective tools for state regulation of innovative activity in the field of green economy, namely: tax incentives, increased state financing of technological and innovative activities, development of innovation-oriented culture. Also the role of energy innovations in relation to sustainable development and the green economy outlined by the authors in the concluding section of the article.